Exercise role in improving the immune system and physical fitness during Corona pandemic period and associated exercise guidelines - Sajad Ahmadizad; Minoo Bassami (Shahid Beheshti University, 2020)
A novel virus that expanded globally from China known as severe acute respiratory syndromecoronavirus 2 (SARS-CoV-2), causing Corona Virus Disease 2019 (COVID-19). Based on the pandemicand fast spreading characteristics of corona virus (COVID-19), it causes concerns for elderly individualsand those with chronic diseases. To lower the chances of spreading the coronavirus, and preventingthe social and economic burden, most of the credible medical centers and organizations haverecommended social distancing and isolations. Disclosure of gyms and sport centers and isolation hasresulted in inactivity in different individuals. The corona virus disease has led to challenges for keepingthe active lifestyle and it can induce some diseases due to inactivity such as obesity metabolicdisorders (e.g., diabetes), cardiovascular diseases, and other diseases that can increase hospitalreferral. Since this is a novel disease and although the effects of regular exercise on it has not beeninvestigated yet, exercise and active lifestyle through increasing energy expenditure, bodymetabolism, and improving physical and psychological fitness can result in increasing health, reducingvirus infection and in the case of having the corona disease it helps a quicker recovery. Since, coronadisease influences on the immune and cardiorespiratory system and the person's physical fitness canbe effective in tolerating the disease side effects, this article expands on the effects of regular exerciseon immune system, viral infections (inflammation), cardiorespiratory system and physical fitness andat the end presents exercise guidelines for different populations.